(untitled) (REMUNOM, 2026)
This article discusses the importance of popular culture in the educational practices of preschool teachers, with an emphasis on how this approach enriches education and promotes more meaningful learning. Through popular culture, which reflects the ways in which different social groups, including children, women and men, interpret and represent the world, teachers can better connect pedagogical content with the reality experienced by children. This is particularly important in Early Childhood Education, where learning should be engaging and relevant to children’s daily lives. The research, carried out with teachers from a public school in Paraná, Brazil, adopted the participant methodology, where the teachers themselves contributed their experiences and narratives in a study group. Through this process, it was realized that incorporating popular culture into teaching practices not only enriches the curriculum, but also promotes a greater connection between the school and the community. In addition, it contributes to the development of an education that values different ways of knowing and living, promoting a more inclusive and meaningful teaching practice for everyone involved. The use of popular culture in educational practices transforms the prescribed curriculum, which can often seem distant from the students’ reality, into something more contextualized and dynamic. This allows both teachers and students to find new meanings in their school experience, strengthening the links between school, culture and social reality.